(untitled) (BSAA arte, 2023)
The parish church of St James the Apostle and St Elizabeth of Portugal of the village of Benijófar, in the province of Alicante, preserves a set of 17th- and 18th-century altarpieces that remains unknown to the historiography. They are an interesting example of the introduction of Baroque art in the territories of the former government and bishopric of Orihuela. This study presents not only the conservation of these unpublished works, but also their origin, which is the church of the Jesuit college in Alicante.